EFFECT OF HERBICIDES ON WEED CONTROL AND YIELD OF WET SEEDED RICE (ORYZA SATIVA L.) - MALLIKARJUN; A. S. CHANNABASAVANNA; SAUNSHI, SUDHEENDRA; C. S. SHRINIVAS (The Bioscan, 2014)
To study effect of herbicides on weed control and yield of wet seeded rice which involves three pre-emergent herbicides viz., butachlor, anilophos and oxyflurofen applied as alone and each these followed by two post emergent herbicides 2, 4- sodium salt, bispyribac sodium and one hand weeding at 25 days. The results revealed that sequential application of butachlor and anilophos fb bispyribac sodium, 2, 4-D sodium salt and one hand weeding at 25 days was recorded significantly lower weed population and dry weight of weeds viz., monocots, dicots and sedges in equal manner which ultimately indicates that higher weed control efficiency over rest of the treatments except weed free check and hand weeding thrice. further, grain and straw yield of rice was followed the same trend as well influenced by yield parameters like number of panicles per sq.m and number of seeds/ panicle ultimately sequential application butachlor and anilophos fb 2, 4-D sodium salt and bispyribac sodium and one hand weeding at 25 DAS resulted higher grain yield and profitable rice production.